Effect of Graphite Oxide on the Catalytic Behavior of (S)-Selective Amine Transaminases - Kaloudis, Nikolaos; Zygouri, Panagiota; Chalmpes, Nikolaos; Spyrou, Konstantinos; Gournis, Dimitrios; Pavlidis, Ioannis V. (Frontiers in Catalysis, 2022)
Graphite oxide (GO) has been used for the immobilization of several classes of enzymes, exhibiting very interesting properties as immobilization matrix. However, the effect the nanomaterial has on the enzyme cannot be predicted. Herein, the effect GO has on the catalytic behavior of several (S)-selective amine transaminases ((S)-ATAs) has been investigated. These enzymes were the focus of this work as they are homodimers with pyridoxal 5’-phosphate in their active site, significantly more complex systems than other enzymes previously studied. Addition of GO (up to 0.1 mg/mL) in the reaction medium leads to activation (up to 50% improved activity) for most enzymes studied, while they maintain their temperature profile (they perform better between 40-45ºC), and their stability. However, the effect is not universal and there are enzymes that are negatively influenced by the presence of the nanomaterial. More profound is the effect on the (S)-ATA from Chromobacterium violaceum which loses almost 50% of its activity in the presence of 0.1 mg/mL GO, while the stability was significantly decreased, losing its activity after 2 h incubation at 40°C, in the presence of 25 μg/mL GO. This negative effect seems to rise from minor secondary structure alterations; namely, a loss of α-helices and subsequent increase in random coil ( 3% in the presence of 25 μg/mL GO). We hypothesize that the effect the GO has on (S)-ATAs is correlated to the surface chemistry of the enzymes; the less negatively-charged enzymes are deactivated from the interaction with GO. This insight will aid the rationalization of ATA immobilization onto carbon-based nanomaterials.